ANALYSIS OF ACCOUNTING STUDENTS' UNDERSTANDING OF THE DEVELOPMENT OF BASIC ACCOUNTING CONCEPTS AND THEIR APPLICATION - Putri Safitri; Afrizal Nilwan (ZILLZELL MEDIA PRIMA, 2024)
This study examines the understanding of students majoring in Accounting related to the development of basic accounting concepts and their implementation in teaching at several universities in Bandar Lampung. S1 Accounting students from Bandar Lampung University, Technocrat University, and Darmajaya University class of 2020 became research subjects. Qualitative methods are used with data collection through questionnaires. The results showed differences in student understanding related to basic accounting concepts, influenced by teaching approaches, curricula, and learning methods at each university. Data analysis uses a descriptive approach with percentage-based score interpretation. The implications of this research can be used to improve teaching effectiveness and student understanding of basic accounting concepts. Further research recommendations include analysis of additional variables and company types to understand holistically the challenges of a dynamic and competitive work environment. These findings support the development of a responsive and relevant curriculum in meeting industry demands.